Study of knowledge, attitude and practices of contraception among the married women of reproductive age group in rural area - Melkani, Deepshikha; Jain, Nikita; Masand, Deepa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: More than 40% of pregnancies worldwide are unintended leading to either an unplanned birth or unsafe abortions and maternal morbidity. India, being the most populous country, have an inherent requirement of knowing KAP of contraception among women of reproductive age to prevent unplanned pregnancies, so as to achieve optimal pregnancy outcome. Methods: A descriptive type of observational cross sectional study, involving 400 women within 18-45 year age group, were interviewed regarding KAP for various contraceptive methods. Results: Statistical analysis of data was done by using chi-square technique. Majority (82.5%) in our study had heard of contraception. In our group, 66.36% had fair knowledge, 31.21% had poor knowledge and 2.42% had good knowledge. Age, education, parity, age at marriage, association of these factors were statistically not significant. Majority (86.06%) had a negative attitude towards contraception because of rural background. Only Age (>20) was found to statistically significant for attitude towards contraception. Our study showed 43.25 % women were currently using contraceptive method, where tubal ligation was most common. Socio-demographic factors like age, education status, age at marriage were found to be statistically significant with practice or usage of contraception. Conclusions: Our study reveals that despite of fair knowledge, majority of women had negative attitude towards contraception, mainly due to rural setup, ignorance, shy nature and family pressure. Despite of fair knowledge about contraceptive methods, there usage is low. Thus, there is need for aggressive advocacy about female reproductive health with dissemination of information about family planning methods among reproductive female.